(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
This study reviews the pioneering work of Gopal Pandey and his influential textbook "Wyakta Chandrika" in shaping Mathematical education in Nepal. Beginning with an overview of the historical context of education in Nepal, including the establishment of formal schooling and the contributions of early scholars, the research focuses on Pandey’s life and his journey as a Mathematician. It examines the content and significance of "Wyakta Chandrika," highlighting its role in imparting Mathematical knowledge and fostering cultural awareness among students. Additionally, the study analyzes the impact of Pandey’s innovative methods, such as the trinomial method for finding cube roots, and explores the evolution of Mathematical literature in Nepal following the publication of "Wyakta Chandrika." Through an analysis of the book’s contents and its implications for Mathematical education, this research provides insights into the enduring legacy of Pandey’s work and its continued relevance in contemporary Nepali Mathematics.